Development and characterization of Haemophilus influenzae type b conjugate vaccine prepared using different polysaccharide chain lengths. Issue 23 (28th May 2015) - Rana, R.; Dalal, J.; Singh, D.; Kumar, N.; Hanif, S.; Joshi, N.; Chhikara, M.K.
Highlights: Hib polysaccharide (PRP) has been reduced to different molecular sizes (10 kDa, 50 kDa and 100 kDa) by oxidation with sodium metaperiodate under controlled conditions. PRP–TT conjugates were prepared using PRP of different sizes and activated tetanus toxoid using reductive amination as conjugation chemistry. The conjugates were purified to remove unreacted polysaccharide and analyzed to determine PRP to protein ratio and amount of free PRP. The conjugates have been tested for immunogenicity in female Sprague Dawley rats by 3 subcutaneous immunizations. The serum IgG titres determined in several studies showed effect of varying chain length of PRP and the 10 kDa PRP–TT conjugates were found to be superior to 50 and 100 kDa PRP–TT conjugates and comparable or better to the licensed vaccines tested. Abstract: Capsular polysaccharide conjugates of Haemophilus influenzae type b (Hib) are important components of several mono- or multi-valent childhood vaccines. However, their access to the most needy people is limited due to their high cost. As a step towards developing a cost effective and more immunogenic Hib conjugate vaccine, we present a method for the preparation of Hib capsular polysaccharide (PRP)–tetanus toxoid (TT) conjugates using optimized PRP chain length and conjugation conditions. Reactive aldehyde groups were introduced into the polysaccharides by controlled periodate oxidation of the native polysaccharide, which were subsequently covalently linked to hydrazide derivatized tetanus toxoid by means of reductive amination. Native polysaccharides were reduced to average 100 or 50 kDa polysaccharide and 10 kDa oligosaccharides in a controlled manner. Various conjugates were prepared using Hib polysaccharide and oligosaccharide yielding conjugates with polysaccharide to protein ratios in the range of 0.25–0.5 (w/w) and free saccharide levels of less than 10%. Immunization of Sprague Dawley rats with the conjugates elicited specific antibodies to PRP. The low molecular weight PRP–TT conjugates were found to be more immunogenic as compared to their high molecular weight counterparts and the PRP–TT reference vaccine.